Peran Literasi Keuangan, Inklusi Keuangan dan Tingkat Pendidikan Terhadap Keberlangsungan Usaha UMKM - Wildan Yusuf, Muhammad; Hidayat, Imam (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
This study aims to analyze the influence of financial literacy, financial inclusion and education level on business sustainability in MSME actors in Tangerang Regency. The method used is a quantitative approach with multiple regression analysis techniques with SPSS version 25. The research sample consisted of 94 respondents selected using the Accidental Random Sampling technique which was distributed online. The results of the study showed that the independent variables, namely financial literacy, financial inclusion and education level, all three have a significant influence on business sustainability. These results indicate that financial inclusion and literacy of business owners contribute positively to business performance. Knowledge of both increases business sustainability, while decreased understanding can reduce performance. The success of MSMEs depends not only on formal education, but also on financial understanding.